Industrial training report: Bank Rakyat / Siti Nurfatin Nabihah Abdul Hakim - Abdul Hakim, Siti Nurfatin Nabihah Abdul Hakim (Faculty of Business and Management, 2025)
During my internship at Bank Rakyat, I had the privilege of gaining practical experience in the MSME Business Support Department, contributing to various administrative and operational activities. This internship provided me with valuable insights into the banking industry, particularly in the areas of Islamic finance and customer-centric banking services. Throughout my tenure, I was actively involved in tasks such as preparing letters of offer, creating memorandums, managing document workflows, and assisting in the organization and delivery of critical documents across departments. These responsibilities enhanced my understanding of banking operations, attention to detail, and adherence to compliance protocols. In addition to hands-on tasks, I observed the bank's strategic positioning through a SWOT analysis, identifying its strengths, weaknesses, opportunities, and threats. Bank Rakyat’s strong reputation as Malaysia’s largest Islamic cooperative bank, coupled with its comprehensive product range and customer-focused approach, positions it well in the competitive banking landscape. However, challenges such as technology gaps, limited international presence, and manpower shortages must be addressed to maintain its market leadership. The experience also highlighted the bank’s potential to capitalize on opportunities in the growing demand for Islamic banking, digital banking innovations, and the expanding SME sector. At the same time, the need to mitigate external threats such as regulatory changes, economic instability, and cybersecurity risks is critical for sustaining long-term success. Overall, my internship at Bank Rakyat was an enriching experience that allowed me to develop professional skills, gain industry knowledge, and contribute meaningfully to the organization. This report provides a comprehensive account of my activities, observations, and learning outcomes, reflecting the significant value of my internship in shaping my career aspirations.